The Theory of Positivism in Islamic Education, Curriculum and Learning Strategies - Supratama, Riky; Ramadani, Mega Melani; Fadilah, Hanura Dewi (Yayasan Azhar Amanaa Yogyakarta, 2024)
Speaking of philosophical concepts of every field of science, including Islamic education focused on one of the philosophies that is positivism. The thinking of positivism has brought great progress in the advancement of science, especially for Islamic education. This can be seen in the development of curriculam and learning strategies that use the basics of positivism philosophy. For example, there is an induction method used in the 2013 curriculum that is very compatible with the method developed by Comte. Therefore, this writing is as an initial, even global, attempt to see how positivist paradigms are applied in the world of education. This research is included in the library research, that is, research that limits research and data search only through library collections without requiring research and field data. In this research, researchers use qualitative research methods. In the library research that uses qualitational methods, they take the necessary data from sources such as books, journals, articles.